JKN System Development Strategy as a Solution to BPJS Health Deficit at Abdoel Wahab Sjahranie Hospital - Sumarni Sumarni; Nur Asiza; Ulia Fitri (Indonesian Journal of Wiyata Health Administration (IJWHA), 2022)
The JKN system includes various types of health services, such as preventive services, health promotion, curative services, rehabilitative, and others. This study seeks to analyze the strategy of implementing the JKN system development as a solution to the deficit of BPJS Kesehatan RSUD Abdoel Wahab Sjahranie. The research used is qualitative research through Focus Group Dicussion. The JKN system development strategy in overcoming the BPJS Kesehatan deficit at Abdoel Wahab Syahranie Hospital can be formed through internal hospital governance to overcome fraud in health action services at the hospital. The application of the swot analysis strategy can be realized through the hospital's annual work plan. Recommendations for further research can conduct research on the governance of BPJS claims in order to minimize fraud.